INTERNALISASI NILAI PENDIDIKAN KARAKTER HINDU PADA ANAK USIA DINI DI TAMAN KANAK-KANAK JAMBE KUMARA KABUPATEN GIANYAR - Arsini, Ni Wayan; Srie Kusuma Wardhani, Ni Ketut; Komang Sutriyanti, Ni (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The formation of a child's character starts from an early age, namely in the family environment which is the first and foremost vehicle for children's character education before going to an educational institution. Jambe Kumara Kindergarten is one of the early childhood formal education institutions in the Gianyar Regency. Jambe Kumara Kindergarten only has teachers with an early childhood teacher education background. The Jambe Kumara Kindergarten Teacher has no special expertise in the field of religious education. The problems that will be examined in this study are: (1) How is the process of internalizing the value of Hindu character education in early childhood Jambe Kumara Kindergarten Gianyar Regency ?, (2) What obstacles do PAUD teachers face in internalizing the value of Hindu character education in early childhood Jambe Kumara Kindergarten Gianyar Regency ?, then (3) What is the impact of internalizing the value of Hindu character education on early childhood Jambe Kumara Kindergarten in Gianyar Regency?. The theory used in this study are: (1) Social Learning Theory from Albert Bandura, (2) Cognitive Learning Theory from Jean Piaget, and (3) Motivation Theory from Maslow and McLelland. The method used to collect data is non-participant observation methods, structured interviews, library studies, and documentation. The collected data was then analyzed with qualitative descriptive techniques. The results of this study indicate (1) the process of internalizing the value of Hindu character education in early childhood Jambe Kumara Kindergarten in Gianyar Regency is carried out through (a) habituation, (b) exemplary (Modeling), (c) School Culture Development, and (d ) Extracurricular activities. (2) The obstacles faced by PAUD teachers in internalizing the value of Hindu character education in early childhood Jambe Kumara Kindergarten in Gianyar Regency are in the form of internal factors and external factors. (3) The impact of internalizing the value of Hindu character education in early childhood Jambe Kumara Kindergarten Gianyar Regency is the formation of the character of early childhood believers / religious (sradha), discipline (yoga sadhana), independent (rtvig rtvijam), and friendly (samiksantam).